PRINCIPALS' TRANSFORMATIONAL LEADERSHIP ON THE IMPLEMENTATION OF THE INDEPENDENT CURRICULUM IN ELEMENTARY SCHOOLS - Yuliana, Lailatul; Rindaningsih, Ida (Academic Journal Research, 2024)
Abstract In building the growth of a nation, education is very important. As a school principal, it is the principal's responsibility to ensure that students learn well so that the country can achieve its goals and advance its culture. Principals do not only function as administrative officials who sign off on policies, but also play an important role in building the ethos of the institution and planning its future direction. The purpose of this study is to provide school principals with some ideas and insights into the different types of leadership and communication patterns they can use to achieve their set learning goals in order to adapt to the current state of education, taking into account all the points from the description given above. This investigation utilized a literature review methodology, which falls under the category of qualitative research. Based on the discussion given, it can be concluded that a principal's social communication skills have a significant effect on leadership effectiveness and problem solving in the classroom. Keywords: education, principal, and learning.